Personality and use of computer in computing engineering students - Arias Gallegos, Walter Lizandro (2016)
In the present study we analyze relations among personality and the computer time of using among university students of computing engineering. We work with a sample of 67 students from a private university located in Arequipa City, who fill a brief survey and the Eysenck Personality Inventory. The results show 44.7% of students are sanguine personality type the most of students dedicate more time using computers to get fun. Although, we did not find relations between the use of computer and personality.